مؤشرات تطبيق المعايير البيئية في صناعة الإسمنت حالة الدراسة: معمل اسمنت طرطوس - عوض عادل; سلمان هناء; علي نبيلة (Latakia University Journal -Engineering Sciences Series, 2019)
تحدد مؤشرات تطبيق المعايير البيئية في صناعة الإسمنت استراتيجية المعالجة وأولويات الإنفاق على الاستثمارات البيئية من أجل تخفيف التدهور البيئي الناتج عن هذه الصناعة باستخدام التحليل الاقتصادي البيئي بحيث تتحقق أكبر منفعة بيئية واقتصادية. وقد تم في هذا البحث تقدير تكاليف التدهور البيئي وعدم الكفاءة (Damage and Inefficiency Costs (CDI وحساب تكاليف المعالجة Remediation Costs (RC) الضرورية في منطقة المعمل والمناطق المجاورة له في المجالات البيئية (الماء, الهواء والضجيج, التربة والمناظر الطبيعية, النفايات, الطاقة والمواد الأولية, البيئة العالمية), وكذلك تم حساب الخسائر الاقتصادية من خلال التصنيفات: (الصحة ونوعية الحياة, الثروة الطبيعية, عدم الكفاءة في استخدام الموارد الطبيعية) لعام 2006 الناتجة عن الإدارة البيئية غير الملائمة للنفايات الصلبة والسائلة والغازية الناتجة عن صناعة الإسمنت, إضافة إلى تحديد أولويات المعالجة في المجالات المذكورة سابقاً. وتم تمثيل النتائج كنسبة مئوية من القيمة المضافة لشركة اسمنت طرطوس عام 2006. وتبين أن إجمالي تكاليف الضرر وعدم الكفاءة وتكاليف الضرر على البيئية العالمية بلغ حوالى (36,19%) من القيمة المضافة, وأكبر قيمة ضرر منها كانت في مجال الطاقة والمواد الأولية حيث بلغت قيمته (14,6%). The indicators of applying the environmental standards in the cement industry indicate the remediation strategy and the priorities of environmental investments expenditures in order to reduce the environmental degradation resulted from this industry, by using environmental economic analyses in order to achieve the biggest economic environmental benefit. In this study the costs of environmental degradation, as well as the costs of necessary remediation in the plant and its surrounding area have been evaluated by environmental domains (Water, Air and Noise, Soils and Landscape, Waste as well as Energy and Materials, global environment), and also by economic categories (Health and Quality of life, Natural capital and finally Inefficiencies) resulted from inadequate environmental management of liquid and solid waste and gas emissions generated by cement industry in the reference year 2006, and the priorities order of environmental remediation in the domains and categories mentioned above has been set. The results are presented in percentage of Tartous Cement Company’s VA (Value Added) (2006). The aggregate damage, inefficiency, and the damage on global environment costs (DIC) amount to 36.19% of VA, from which the maximum damage was in the domain of inefficiency in raw materials and energy that present 14.6 %.